Improving the livelihoods of poor livestock-keepers in Africa through community-based management of indigenous farm animal genetic resources: 2004 Progress Report - International Livestock Research Institute (2005)
The goal of the project is to improve the livelihoods of poor livestock-keepers through the conservation and sustainable use of indigenous animal genetic resources. The purpose is the empowerment of local communities, through an improvement of their analytical, technical, managerial and organisational skills to sustainably manage AnGR, in order to reduce poverty and food insecurity. Outputs will include: 1) A framework for community-based management (CBM) of AnGR developed, its operational components tested and at least one program established and functional in each project country by the end of the project period; 2) Market opportunities for indigenous livestock quantified and institutional constraints to commercialisation and marketing identified; 3) Producer and consumer preferences for alternative livestock genotypes (and associated products) quantified, and cost-benefit analysis of alternatives conducted and results used to inform policy discussions and development; 4) Policy constraints to conservation and sustainable use of indigenous livestock identified and policy recommendations made to address the constraints and improve opportunities for poor livestock-keepers to derive increased benefits from their livestock; 5) Policy-makers sensitised to community needs and facilitate the formulation and implementation of essential policy instruments, as a result of their participation in project